2004
DOI: 10.1001/jama.291.24.2969
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Gene Polymorphisms and Risk of Myocardial Infarction

Abstract: ContextThe role of estrogens in ischemic heart disease (IHD) is uncertain. Evidence suggests that genetic variations in the estrogen receptor ␣ (ESR1) gene may influence IHD risk, but the role of common sequence variations in the ESR1 gene is unclear.Objective To determine whether the ESR1 haplotype created by the c.454-397TϾC (PvuII) and c.454-351AϾG (XbaI) polymorphisms is associated with myocardial infarction (MI) and IHD risk. Design, Setting, and ParticipantsIn 2617 men and 3791 postmenopausal women from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
157
4
5

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(173 citation statements)
references
References 52 publications
7
157
4
5
Order By: Relevance
“…Three large, well-designed and well-implemented studies were published with apparent contradictory results in relation to ESR1 IVS1-397T>C polymorphism and myocardial infarction (9)(10)(11). In relation to ESR1 IVS1-397T>C polymorphism and lipid levels, Demissie et al (12) demonstrated an association between IVS1-397T>C polymorphism T/T genotype and LDL-C particle size reduction in women from the Framingham Heart Study.…”
Section: Discussionmentioning
confidence: 99%
“…Three large, well-designed and well-implemented studies were published with apparent contradictory results in relation to ESR1 IVS1-397T>C polymorphism and myocardial infarction (9)(10)(11). In relation to ESR1 IVS1-397T>C polymorphism and lipid levels, Demissie et al (12) demonstrated an association between IVS1-397T>C polymorphism T/T genotype and LDL-C particle size reduction in women from the Framingham Heart Study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous analyses we chose haplotype 1 as the risk allele (9,11,16,21,22). To account for possible confounding, we adjusted the analysis of sex hormone levels for age, BMI, years since menopause and the direct precursor for each hormone when available.…”
Section: Discussionmentioning
confidence: 99%
“…Of the polymorphisms identified so far, the PvuII and XbaI SNPs, located in the first intron 397 and 351 bp upstream of exon 2, are the most widely studied. These polymorphisms have previously been associated with disease phenotypes such as osteoporosis (7 -10), cardiovascular disease (11,12) and cancer (13). Recently a potential functional significance of the PvuII polymorphisms was reported (14).…”
Section: Introductionmentioning
confidence: 99%
“…2 All SNPs were genotyped with Taqman Assays-by-Design SNP Genotyping Service and ABI PRISM s 7900HT Sequence Detection System (both: Applied Biosystems). The association of the ERa haplotype with depressive symptoms, and depressive disorders, and anxiety was assessed separately in men and women using logistic regression and testing an allele-dose model.…”
mentioning
confidence: 99%
“…2 The translocation leads to an interference in the open reading frame of the Disrupted-in-Schizophrenia-1 (DISC1) gene that could produce a C-terminal truncated DISC1 protein. In a previous study, we conducted a yeast two-hybrid screening in order to identify possible protein interactors involved with cellular signaling of DISC1.…”
mentioning
confidence: 99%